AAV-Mediated GALC Gene Therapy Rescues Alpha-Synucleinopathy in the Spinal Cord of a Leukodystrophic Lysosomal Storage Disease Mouse Model - Marshall, Michael S.; Issa, Yazan; Heller, Gregory; Nguyen, Duc; Bongarzone, Ernesto R. (Frontiers in Cellular Neuroscience, 2020)
Krabbe’s disease (KD) is primarily a demyelinating disorder, but recent studies have identified the presence of neuronal protein aggregates in the brain, at least partially composed by alpha-synuclein (alpha-syn). The role of this protein aggregation in the pathogenesis of KD is largely unknown, but it has added KD to a growing list of lysosomal storage diseases that can be also be considered as proteinopathies. While the presence of these protein aggregates within the brain is now appreciated, the remainder of the central nervous system (CNS) remains uncharacterized. This study is the first to report the presence of thioflavin-S reactive inclusions throughout the spinal cord of both murine and human spinal tissue. Stereological analysis revealed the temporal and spatial accumulation of these inclusions within the motor neurons of the ventral horns versus the sensory interneurons located in the dorsal horns. This study also confirmed that these thio-S positive accumulations are present within neuronal populations and are made up at least in part by alpha-syn in both the twitcher mouse and cord autopsied material from affected human patients. Significantly, neonatal gene therapy for galactosylceramidase, a treatment that strongly improves the survival and health of KD mice, but not bone marrow transplantation prevents the formation of these inclusions in spinal neurons. These results expand the understanding of alpha-syn protein aggregation within the CNS of individuals afflicted with KD and underlines the tractability of this problem via early gene therapy, with potential impact to other synucleinopathies such as PD.